Integrated Exergetic and Exergoeconomic Evaluation of Teak, Matoa, and Merbau Wood Waste for Charcoal Production in a Laboratory-Scale Modified Fixed-Kiln Reactor - Joni, Joni; Kaiway, Mickael Ruben; Tambing, Enos (Engineering, Technology & Applied Science Research, 2026)
This study introduced a batch-level exergy-exergoeconomic diagnostic framework for evaluating charcoal production in a laboratory-scale, modified fixed-kiln reactor. Unlike yield- based or energy-only assessments, the proposed approach, considers exergy destruction and its associated economic penalty, allowing for direct comparisons of feedstock performance under identical operating and cost conditions. Three wood residues were examined: teak (Tectona grandis), matoa (Pometia pinnata), and merbau (Intsia spp.). The analysis revealed that merbau is the superior feedstock, achieving the highest exergetic efficiency (43.2%) and char yield (92.3%) at the lowest peak temperature (285°C). This is in contrast to matoa, which achieved 35.0% efficiency at 429°C, and teak, which achieved 32.4% efficiency at 374°C. Economically, the study revealed that feedstock selection significantly impacts costs: Merbau exhibited the lowest specific production cost ($1.08/kg) and the lowest cost of exergy destruction ($0.47 per batch). In contrast, teak produced the highest costs ($1.91/kg; $0.64 destruction) due to substantial internal irreversibility (82.3 MJ/batch). By linking thermodynamic irreversibility directly to cost formation, this methodology shows that maximizing the reactor temperature does not guarantee efficiency. It also provides a metric that can be used to select the most suitable feedstock for small-scale biomass carbonization systems.